Performance of spleen stiffness measurement by 2D-shear wave elastography in evaluating the presence of high-risk varices: comparative analysis of idiopathic portal hypertension versus hepatitis B virus - Huihui Zhou; Zhilin Zhang; Jun Zhang; Lin Sang; Lina Liu; Xue Gong; Yuanyuan Sun; Yu Zheng; Ming Yu (BMC Medical Imaging, 2023)
Abstract Background Noninvasive assessment of high-risk varices (HRV) in idiopathic portal hypertension (IPH) is rare. The purpose of this study was to investigate the performance of spleen stiffness (SS) for evaluating the presence of HRV in IPH patients as compared the measurements in patients with hepatitis B virus (HBV). Methods A retrospective single-center study was performed to evaluate the performance of SS for assessing HRV in IPH and HBV-infected patients, in comparison with liver stiffness (LS), spleen stiffness-to-liver stiffness ratio (SS/LS), LS spleen-diameter-to-platelet-ratio score (LSPS), portal hypertension risk score (PH risk score) and varices risk score, by using upper gastrointestinal endoscopy (UGE) as the gold standard. Finally, 86 IPH and 102 HBV-infected patients were enrolled. UGE, two-dimensional shear wave elastography (2D-SWE) and laboratory data were collected, and noninvasive parameters were calculated. Analysis of receiver operating characteristic (ROC) curves was conducted to acquire the optimal area under the ROC curve (AUC) and cutoff value for predicting the presence of HRV. Results In patients with HRV, the significantly different parameters between IPH (34.9%) and HBV-infected patients (46.1%) were as follows: spleen size (diameter 18.5 ± 3.9 cm vs. 20.8 ± 2.7 cm), SS (50.2 kPa vs. 42.9 kPa), LS (11.1 kPa vs. 18.3 kPa) and PT (prothrombin time 15.1 s vs. 16.7 s). No statistically significant differences were found in liver function, platelet counts, spleen thickness and flow volumes in the portal venous system (p > 0.05). The AUCs of SS were 0.98 and 0.96 for predicting the presence of HRV in IPH (44.0 kPa cutoff value; 0.93 sensitivity; 0.96 specificity) and HBV-infected patients (35.2 kPa cutoff value; 1.00 sensitivity; 0.82 specificity), respectively, which were significantly better than other parameters. Conclusion SS shows the optimal overall performance for predicting the presence of HRV in IPH and HBV-infected patients, in comparison with other noninvasive parameters.